MEMAHAMI PROBLEMATIKA HAK PENGELOLAAN TANAH KOTA BATAM Dalam Rangka Penetapan Batam sebagai Kawasan Ekonomi Khusus - Nur Hadiyati (Fakultas Hukum Universitas Islam Malang, 2019)
AbstractLand is part of the surface of the earth that plays an important role in the life of the people whose control is in the state, one of the forms of state control over land is the management rights. Batam Island is a sucessful example of management rights on land. However, with the presence of the local governemnt, many new issues about the management of law are feared to emerge. The Management Rights on Batam’s land is obtained directly by the President who delegated to the Board of Mastery, so that the status of Batam land is divided into three namely: (1) the land above the management right by Enterprise (in Indonesian we called it Badan Pengusahaan); (2) land above the management of Batam City Local Government; (3) land managed by the state. Dualism of authority to manage Batam’s Land caused problems as follows: Establishment of Kampung Tua, Status quo on land in Rempang Galang area, mismatch of land condition in Batam City with letter of decision by Ministry of Forestry, and the complexity of permit process, which hampered the development of Batam City. So by understanding how the implementation of Management Rights on Land will be enlightment to find a solution to the problem of dualism of land management authority and formulate the right policy in the framework of determining Batam as a Special Economic Zone.Keywords : Batam, Management Rights, Agrarian, Special Economic Zone, Abstrak Tanah merupakan bagian permukaan bumi yang memegang peranan penting dalam kehidupan masyarakat yang penguasaannya diatur oleh negara, salah satu wujud penguasaan negara atas tanah adalah Hak Pengelolaan. Pulau Batam adalah salah satu contoh HPL “sukses”. Namun, dengan hadirnya pemerintah kotamadya Batam, dikhawtirkan banyak persoalan baru di bidang pertanahan yang muncul. Hak Pengelolaan Batam diperoleh langsung oleh Presiden yang dilimpahkan kepada Badan Penguasaan, sehingga status tanah Batam terbagi atas tiga yaitu : (1) tanah diatas Hak Pengelolaan Badan Pengusahaan; (2) tanah diatas pengelolaan Pemerintah Daerah Kota Batam; (3) tanah pengelolaan negara. Dualisme kewenangan pengelolaan lahan terjadi di Kota Batam dan menimbulkan permasalahan sebagai berikut : penetapan Kampung Tua, Status quo pada tanah dikawasan Rempang Galang, ketidakcocokan kondisi pertanahan di Kota batam dengan SK KEMENHUT, serta kerumitan proses perizinan, yangmana menghambat perkembangan Kota Batam. Maka dengan memahami bagaimana penyelenggaran Hak Pengelolaan dapat menemukan penyelesaian permasalahan dualisme kewenangan pengelolaan lahan dan merumuskan kebijakan yang tepat dalam rangka penetapan Batam sebagai Kawasan Ekonomi Khusus.Kata Kunci : Batam, Hak Pengelolaan, Tanah, Agraria, Kawasan Ekonomi Khusus.